Calibration of Managerial Resilience Strategies in Anticipating Global Supply Chain Disruptions within Export-Oriented Manufacturing Firms - Liana, Lani (Smart International Management Journal, 2024)
The global export manufacturing landscape is currently navigating a state of "polycrisis," where systemic supply chain disruptions pose an existential threat to organizational endurance. This research addresses the critical need for "Managerial Resilience Calibration" a process of precision-tuning organizational strategies based on real-time data to safeguard export continuity. Utilizing a longitudinal quantitative approach, this study analyzes secondary data from 78 export-oriented manufacturing firms listed on the Indonesia Stock Exchange (IDX), integrated with macro-logistical reports from the Central Bureau of Statistics (BPS) and the Ministry of Industry (2021–2024). The results indicate that firms implementing "Active Calibration" characterized by a Resilience Investment Ratio (RIR) exceeding 20% and a Supplier Concentration Index (HHI) below 0.40 maintained 30% higher export stability compared to those following static, cost-centric paradigms. Statistical testing further validates that technological investment and geographical supplier diversification are significant predictors of export resilience (). This study concludes that a shift from pure cost-efficiency toward resilience-based effectiveness is mandatory for international competitiveness. These findings advance the dynamic capabilities framework by quantifying the calibration mechanism through empirical corporate performance.